EVALUASI PENERAPAN K3 PADA PEKERJAAN PROYEK PEMBANGUNAN BHISA PLAZA CIREBON - David Wibowo; Arianti Sutandi (Jurnal Serina Abdimas, 2026)
By identifying possible risks and putting preventative measures in place in case of an incident, Occupational Safety and Health (OSH) aims to prevent workplace accidents and occupational diseases. Construction projects are inherently risky, especially when it comes to structural work and demolition, which call for heavy lifting and the use of dangerous machinery. The purpose of this essay is to assess how OSH procedures were applied in the Cirebon building project known as Bhisa Plaza. Direct field observations and document studies pertaining to the OSH processes used during the construction phase were used to conduct the evaluation. Workplace organization, site monitoring mechanisms, and the use of personal protective equipment (PPE) are among the elements that were noticed. According to the evaluation's findings, OSH implementation at the project site has been completed, although it is still not at its best, especially when it comes to safety compliance. There were still a few minor infractions discovered, like employees not always wearing safety shoes or helmets in specific locations and not receiving frequent safety briefings before beginning daily tasks. Low worker awareness and little project inspector on-site supervision are the primary causes of poor OSH implementation. In order to guarantee more efficient OSH implementation and reduce the risk of workplace accidents in upcoming building projects, this research highlights the necessity of improved safety awareness programs, ongoing supervision, and frequent socialization activities.. Keselamatan dan Kesehatan Kerja (K3) bertujuan untuk mencegah kecelakaan kerja dan penyakit akibat kerja dengan cara mengidentifikasi potensi risiko serta menerapkan langkah-langkah pencegahan jika terjadi insiden. Proyek konstruksi memiliki tingkat risiko yang tinggi, terutama pada pekerjaan struktur dan pembongkaran yang melibatkan aktivitas fisik berat serta penggunaan alat berat yang berbahaya. Tujuan dari makalah ini adalah untuk menilai bagaimana penerapan prosedur K3 pada proyek pembangunan Bhisa Plaza di Cirebon. Evaluasi dilakukan melalui observasi langsung di lapangan dan studi dokumen terkait proses penerapan K3 selama tahap konstruksi. Aspek-aspek yang diamati meliputi pengaturan area kerja, mekanisme pengawasan di lapangan, serta penggunaan Alat Pelindung Diri (APD).Hasil evaluasi menunjukkan bahwa penerapan K3 di lokasi proyek telah dilakukan, namun belum sepenuhnya optimal, terutama dalam hal kepatuhan terhadap keselamatan. Masih ditemukan beberapa pelanggaran ringan seperti pekerja yang tidak selalu mengenakan helm atau sepatu keselamatan di area tertentu, serta tidak adanya pengarahan keselamatan (safety briefing) secara rutin sebelum kegiatan kerja dimulai. Rendahnya kesadaran pekerja dan minimnya pengawasan dari inspektur proyek menjadi penyebab utama lemahnya implementasi K3. Penelitian ini menekankan pentingnya peningkatan program kesadaran keselamatan, pengawasan yang berkelanjutan, serta sosialisasi rutin untuk memastikan penerapan K3 berjalan lebih efektif dan dapat meminimalkan risiko kecelakaan kerja pada proyek-proyek konstruksi di masa mendatang..